Molecular chaperones and regulation of tau quality control: strategies for drug discovery in tauopathies. (September 2011) - Miyata, Yoshinari; Koren, John; Kiray, Janine; Dickey, Chad A; Gestwicki, Jason E
Tau is a microtubule-associated protein that accumulates in at least 15 different neurodegenerative disorders, which are collectively referred to as tauopathies. In these diseases, tau is often hyperphosphorylated and found in aggregates, including paired helical filaments, neurofibrillary tangles and other abnormal oligomers. Tau aggregates are associated with neuron loss and cognitive decline, which suggests that this protein can somehow evade normal quality control allowing it to aberrantly accumulate and become proteotoxic. Consistent with this idea, recent studies have shown that molecular chaperones, such as heat shock protein 70 and heat shock protein 90, counteract tau accumulation and neurodegeneration in disease models. These molecular chaperones are major components of the protein quality control systems and they are specifically involved in the decision to retain or degrade many proteins, including tau and its modified variants. Thus, one potential way to treat tauopathies might be to either accelerate interactions of abnormal tau with these quality control factors or tip the balance of triage towards tau degradation. In this review, we summarize recent findings and suggest models for therapeutic intervention.